2 Evaluating the effects of a dietary strategy to mitigate the impact of in utero heat stress on biomarkers of post-absorptive metabolism and stress in pigs following weaning and transport. (30th November 2020) - Maskal, Jacob M; Duttlinger, Alan W; Kpodo, Kouassi R; McConn, Betty R; Byrd, Christopher; Richert, Brian T; Lay, Donald C; Marchant-Forde, Jeremy; Lucy, Matthew; Safranski, Tim; Perry, Shelbi; Johnson, Jay S
Abstract: In utero heat stress (IUHS) increases postnatal energy requirements of pigs, and this may exacerbate weaning and transport stress. The study objective was to evaluate the impact of providing a nutrient dense (ND) diet, which met the greater energy requirements of IUHS pigs, on biomarkers of post-absorptive metabolism and stress following weaning and transport. Twenty-four pregnant gilts were assigned to thermoneutral (n = 12; 17.5 ± 2.1°C) or heat stress (n = 12; cyclical 26°C to 36°C) conditions from gestation d 1 to 58, and then TN conditions until farrowing. At weaning (16.2 ± 0.4 d), mixed-sex piglets (n = 160; 4.78 ± 0.15 kg BW) were transported (loading + transport + unloading) for 11 h 40 min and then blocked into pens (n = 4 piglets/pen) by in utero and dietary treatments fed for 14 d (P1): in utero thermoneutral (IUTN) + control diet (C; n = 10 pens), IUTN + ND (n = 10 pens), IUHS + C (n = 10 pens), IUHS + ND (n = 10 pens). The C diet was fed to all pigs from d 15 to 35 post-weaning and transport (P2). One pig per pen was bled immediately pre-transport (Pre-T) and immediately post-transport (Post-T), and on d 2, 7, 14, 28, and 35 post-weaning and transport to analyze cortisol, glucose, insulin, and non-esterified fatty acids (NEFA). Overall, cortisol was decreased (P = 0.03; 25.8%) during transport in IUHS versus IUTN pigs. On d 2, glucose was decreased overall (P = 0.01; 13.5 mg/dL) in IUHS versus IUTN pigs, but no d 2 insulin (P = 0.76; 0.079 ± 0.011 ng/mL) or NEFA (P = 0.65; 810.3 ± 61.1 mEq/L) differences were detected. Insulin and insulin:glucose ratio were increased (P < 0.04; 0.076 ng/mL and 0.05, respectively) during P1 in ND versus C pigs. In summary, the physiological stress response and glucose levels were altered in IUHS versus IUTN pigs post-weaning and transport, but dietary treatment did not interact with in utero treatment.